WOMEN ENTREPRENEURS AND GOVERNMENT POLICIES: A PATH TO EMPOWERMENT - Ritu Kumari; Singh, Vinay Pal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women play a crucial part in Indian culture; nonetheless, their inferior social standing has hindered their ability to fully actualize their entrepreneurial potential. The MSME sector substantially enhances economic growth in India. The Indian economy is asserted to be strengthened by it. It has provided resilience to deal with shocks and adversities associated with the global economy. Approximately twenty percent of Indian MSMEs are situated in rural regions, where they employ almost 40% of the nation’s workforce. This paper aims to outline the challenges encountered by Indian female entrepreneurs and to delineate the main factors influencing their growth. The article examines several programs launched by the Ministry of MSME and seeks to determine the necessary actions to enhance women’s entrepreneurship in India. It also analyses the available financing sources and the criteria for eligibility to offer financial assistance to Indian women entrepreneurs. It is essential to educate Indian women entrepreneurs on the availability of state and central financial schemes and their funding sources, as well as to provide modest loans or microfinance to women entrepreneurs beginning enterprises in rural and semi-urban areas. The state government and financial institutions will offer development and training programs for educated young women and experienced female entrepreneurs. India is experiencing a significant increase in the population of female entrepreneurs. Consequently, federal and state governments have established financial organizations to support women-owned enterprises. To achieve this goal, they have implemented several programs to alleviate the financial burden on female businesses.